Emergency management of febrile status epilepticus: Results of the FEBSTAT study. Issue 3 (6th February 2014) - Seinfeld, Syndi; Shinnar, Shlomo; Sun, Shumei; Hesdorffer, Dale C.; Deng, Xiaoyan; Shinnar, Ruth C.; O'Hara, Kathryn; Nordli, Douglas R.; Frank, L. Matthew; Gallentine, William; Moshé, Solomon L.; Pellock, John M.; et al.
Summary Objective Treatment of seizures varies by region, with no standard emergency treatment protocol. Febrile status epilepticus (FSE) is often a child's first seizure; therefore, families are rarely educated about emergency treatment. Methods From 2002 to 2010, 199 subjects, age 1 month to 6 years, were recruited as part of a prospective, multicenter study of consequences of FSE, which was defined as a febrile seizure or series of seizures lasting >30 min. The patients' charts were reviewed. No standardized treatment protocol was implemented for this observational study. Results One hundred seventy‐nine children received at least one antiepileptic drug (AED) to terminate FSE, and more than one AED was required in 140 patients (70%). Median time from the seizure onset to first AED by emergency medical services (EMS) or emergency department (ED) was 30 min. Mean seizure duration was 81 min for subjects given medication prior to ED and 95 min for those who did not (p = 0.1). Median time from the first dose of AED to end of seizure was 38 min. Initial dose of lorazepam or diazepam was suboptimal in 32 (19%) of 166 patients. Ninety‐five subjects (48%) received respiratory support by EMS or ED. Median seizure duration for the respiratory support group was 83 min; for the nonrespiratory support group the duration was 58 min (p‐value < 0.001). Reducing the time from seizure onset to AED initiation was significantly related to shorter seizure duration. Significance FSE rarely stops spontaneously, is fairly resistant to medications, and even with treatment persists for a significant period of time. The total seizure duration is composed of two separate factors, the time from seizure onset to AED initiation and the time from first AED to seizure termination. Earlier onset of treatment results in shorter total seizure duration. A standard prehospital treatment protocol should be used nationwide and education of EMS responders is necessary.